1997
DOI: 10.1128/iai.65.12.5346-5348.1997
|View full text |Cite
|
Sign up to set email alerts
|

Interference of peptides and specific antibodies with the function of the Actinobacillus pleuropneumoniae transferrin-binding protein

Abstract: Multiple-antigenic peptides (MAPs) containing transferrin-binding domains of the Actinobacillus pleuropneumoniae serotype 7-derived transferrin-binding protein (TfbA) (K. Strutzberg, L. von Olleschik, B. Franz, C. Pyne, M. A. Schmidt, and G.-F. Gerlach, Infect. Immun. 63:3846-3850, 1995) were constructed. It was found that the MAPs inhibited transferrin binding of the recombinant TfbA protein, whereas antibodies directed against transferrin-binding domains failed to do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Transposon mutagenesis of the tbpB gene revealed that TbpB-binding activity for pTf was retained in a fusion protein containing the first 289 amino acids of the mature protein and a series of randomly generated mutants with reduced binding activity primarily mapped to those regions (Strutzberg et al, 1995). A synthetic peptide library representing TbpB from A. pleuropneumoniae was probed with labeled pTf to reveal peptide regions with Tf-binding activity (Strutzberg et al, 1997). Similar approaches have been used to probe the tight interactions between TbpB and Tf in several human pathogens (Renauld-Monge ´nie et al, 1997;Retzer et al, 1999;Sims and Schryvers, 2003), but a clear understanding and appreciation of this interaction has been elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Transposon mutagenesis of the tbpB gene revealed that TbpB-binding activity for pTf was retained in a fusion protein containing the first 289 amino acids of the mature protein and a series of randomly generated mutants with reduced binding activity primarily mapped to those regions (Strutzberg et al, 1995). A synthetic peptide library representing TbpB from A. pleuropneumoniae was probed with labeled pTf to reveal peptide regions with Tf-binding activity (Strutzberg et al, 1997). Similar approaches have been used to probe the tight interactions between TbpB and Tf in several human pathogens (Renauld-Monge ´nie et al, 1997;Retzer et al, 1999;Sims and Schryvers, 2003), but a clear understanding and appreciation of this interaction has been elusive.…”
Section: Introductionmentioning
confidence: 99%